Monitoring the Hydrothermal Crystallization of Ga/ZSM-5 Using Sorption and other Conventional Techniques - S.V. Awate; P.N. Joshi; T.H. Kim; K.I. Kim; V.P. Shiralkar (Adsorption Science & Technology)
Sorption techniques have been employed for monitoring progress in the hydrothermal crystallization of synthetic MFI-type gallosilicate from a (TEBA) 2 O–Na 2 O–Ga 2 O 3 –SiO 2 –H 2 O system at 453 K. The samples obtained at different stages in the crystallization process were also examined by other conventional techniques such as XRD, IR, TG/DTA, N 2 adsorption and chemical analysis. The influence of the crystallinity on the BET surface area and on the micropore void volume was examined using low-temperature nitrogen adsorption. The sorption uptake behaviour was studied on samples of varying crystallinity using different sorbate probe molecules such as water, n-hexane and cyclohexane. The amount of sorbate uptake was found to be sensitive to the crystallinity of the sample and the characteristics of the probe molecules employed. The crystallinity as estimated by XRD methods has been compared with that obtained by sorption uptake using different probe molecules. In comparison to other sorbates, the uptake of n-hexane was found to yield a more realistic estimation of the degree of crystallization of the intermediate phases. The crystallinity evaluated from the uptake of n-hexane was found to be in close agreement with that estimated by XRD methods as compared to the crystallinity evaluated using other conventional techniques. The correlation between the crystallinity obtained by sorption measurements and by other methods such as XRD, IR, TG/DTA and N 2 adsorption was discussed and compared.